Slip effects on unsteady mixed convection of hybrid nanofluid flow near the stagnation point - Mohd Nazar, Roslinda; Zainal, Nurul Amira; Naganthran, Kohilavani; Pop, Ioan (Springer Science and Business Media B.V., 2022)
The unsteady mixed convection of the Al2O3-Cu/H2O hybrid nanofluid flow near the stagnation point past a vertical plate is analyzed. The bvp4c technique is used to solve the resulting ordinary differential equations. The combined effects of the velocity and thermal slip are addressed. The effects of different relevant physical parameters are studied numerically. The results show that the heat transfer rate is reduced when the volume fraction of the nanoparticles increases, while the unsteadiness parameter has an opposite effect in the opposing flow. The presence of the slip parameter is proven to increase the skin friction coefficient while reduce the local Nusselt number in the buoyancy opposing flow. A contradictory result is observed in the buoyancy assisting flow. Meanwhile, the heat transfer rate is reduced in the buoyancy of the assisting and opposing flows when the thermal slip effect is considered.